Pengaruh Kampanye #onegreenstep Garnier Di Media Sosial Instagram Terhadap Sikap Gen Z Tentang Mendaur Ulang Sampah - Narano, Deo; Abdullah, Nisa Nurmauliddiana (eProceedings of Management, 2024)
From 2021 to July 2022 the number of cosmetics companies increased by 20.6 percent, with an increase from 819businesses to 913 businesses (Febrinastri, 2022). With the increase in the cosmetics industry, the waste produced bycosmetics companies also increases. This made the Garnier brand create an online campaign to increase publicawareness about the state of the environment and encourage people to take concrete action to support environmentalconservation. This research aims to determine the influence and magnitude of the influence of Garnier's#OneGreenStep campaign on Instagram with the dimensions of message content, message structure, message frameon Gen Z's attitudes about recycling waste with cognitive, affective and conative dimensions. This research uses acausal quantitative approach. Data collection was carried out by distributing questionnaires to 400 respondents witha population of Instagram followers @garnierindonesia. The data collection technique in this research uses a nonprobability sampling technique, namely purposive sampling. The research results show that Garnier's #OneGreenStepcampaign has a significant influence on the attitudes of Gen Z with a coefficient value of 0.633. Meanwhile, the resultsof the coefficient of determination of the influence of Garnier's #OneGreenStep campaign on Gen Z's attitudesobtained results of 40%, the remaining 40% were influenced by other factors outside this research. Keywords- campaigns, attitudes,gen Z, social media.